Portraying IFL (BIPA) Class in UIN Maulana Malik Ibrahim Malang: A Somalian Student’s Perspective - Anggarini, Ida Fitri; Noviyanti, Shobihatul Fitroh; Rusdiyana, Athi' Firliya; Darojat, Karimah (ELITE JOURNAL, 2023)
ABSTRACT Indonesian as a Foreign Language or IFL well-known as BIPA is an obligation for foreign learners before being a student in Indonesia’s university, for example in UIN Maulana Malik Ibrahim, Malang, Indonesia. This study aimed to explore the BIPA class at that university by focusing on Somalian students’ perspective. This qualitative study used observation, in-depth interviews, and documentation to collect primary data from five Somalian students. The study revealed that there are many activities at BIPA Class in UIN Maulana Malik Ibrahim, Malang such as combining the lecturer and the tutor in teaching BIPA, various activities, methods, and intensive communication that promote the Somalian students Bahasa Indonesia’s skills (listening, reading, writing and speaking). The findings indicate that BIPA class has a significant impact on Somalian students. Keywords: BIPA Class; Various Strategies; Somalian Student